2022
DOI: 10.3390/cancers14010232
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Growth Factors during Lenvatinib Predict the Post Progressive Survival in Patients with Unresectable Hepatocellular Carcinoma

Abstract: Serum growth factor changes and their effect on prognosis during lenvatinib for unresectable hepatocellular carcinoma (HCC) remain underexplored. The sequential changes in serum growth factors during lenvatinib for unresectable HCC were evaluated in 58 patients using complete clinical data, and preserved serum was used to investigate changes in FGF-19, ANG-2, HGF, VEGF, and EGF. Patients with a complete response (CR), partial response (PR), and stable disease (SD) were evaluated for growth factor changes betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Similarly, recently, Yang et al. reported that higher baseline Ang-2 levels were significantly associated with a nonobjective response in HCC patients treated with lenvatinib ( 73 ).…”
Section: Blood Biomarkersmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, recently, Yang et al. reported that higher baseline Ang-2 levels were significantly associated with a nonobjective response in HCC patients treated with lenvatinib ( 73 ).…”
Section: Blood Biomarkersmentioning
confidence: 86%
“…Miyahara et al (68) described that Ang-2 had a similar predictive function as VEGFA and that Ang-2 levels were significantly elevated in patients with PD prior to sorafenib treatment. Similarly, recently, Yang et al reported that higher baseline Ang-2 levels were significantly associated with a nonobjective response in HCC patients treated with lenvatinib (73). Mechanism and pathways involved in the angiogenesis and proliferation of hepatocellular carcinoma and potential predictive biomarkers.…”
Section: Angiopoietin-2 and Fgf 19/fgf 23mentioning
confidence: 90%
“…Recently, because of successful clinical trials of novel anticancer drugs for unresectable HCC, various systemic therapies, including multikinase inhibitors of sorafenib [ 3 ], lenvatinib [ 4 ], regorafenib [ 5 ], and cabozantinib [ 6 ], a monoclonal antibody targeting vascular endothelial growth factor receptor (VEGFR) 2, ramucirumab [ 7 ], and a combination therapy involving the anti-VEGF-A antibody bevacizumab and the programmed death ligand 1 (PD-L1) inhibitor atezolizumab [ 8 ] have been approved. Real-world data have confirmed the efficacy and safety of those therapies [ 9 , 10 , 11 , 12 , 13 , 14 ]. Of these, atezolizumab and bevacizumab have been recommended as the first-line therapies in various guidelines because they have shown superior overall survival (OS) as compared with the previous standard therapy of sorafenib [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We and other groups have reported that levels of fibroblast growth factors (FGFs), including FGF19 and FGF23, significantly increased after lenvatinib treatment for unresectable HCC [ 12 , 19 ]. Fibroblast growth factor 21 (FGF21) is a member of the FGF19 subfamily, which also includes FGF19 and FGF23.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in systemic therapy have dramatically changed the treatment landscape for unresectable hepatocellular carcinoma (HCC), with prolonged overall survival (OS) [ 1 , 2 , 3 , 4 ]. Various systemic therapies have been developed for unresectable HCC, including the multikinase inhibitors sorafenib [ 1 ], regorafenib [ 5 ], cabozantinib [ 6 ], and lenvatinib [ 2 ], an antibody against VEGFR2, ramucirumab [ 7 ], and the combination of the programmed death ligand 1 (PD-L1) inhibitor atezolizumab and the VEGF inhibitor bevacizumab.…”
Section: Introductionmentioning
confidence: 99%